Potential use of natural phosphate in white oat (Avena sativa L) (Research, Society and Development, 2023)
The objective of this research was to evaluate the efficiency of phosphating with Fosbio® (Rocafeed) in an oat (Avena sativa L) production system in relation to phosphorus and boron contents in the soil in the 0-20 cm and 20-40 cm. The research was carried out at Fazenda Santa Cruz, Rodovia MG 453/Km 13, in the Municipality of Paraguaçu-MG from April to September 2023. The chemical and granulometric parameters of the soil were analyzed, and based on the data obtained, The amount of Fosbio® to be applied to the land was calculated, which was applied by broadcast, followed by the application of natural phosphate and, subsequently, the sowing of white oats (Avena sativa L) in April. The treatments were as follows: T1 - Control, T2 - 500 kg ha-1 of Fosbio® and T3 - 1000 kg ha-1 of Fosbio®. The experiment was installed in a Randomized Block Design (RBD) with 5 replications per treatment, with the parameters evaluated being oat productivity, phosphorus (P) and boron (B) content in the soil before planting and after harvesting in layers of 0 -20 cm and 20-40 cm. The means obtained were compared using the Scott-Knott test with 5% probability, using the SISVAR® software. The application of Fosbio® promoted increases in oat productivity, increased P levels in the soil, through the resin extractor and provided increases in B levels in the soil.